Board profile and earnings quality: Malaysian evidence / Marini Mamat - Mamat, Marini (2011)
This paper examines the association between board profile and earnings quality by using a sample of 113 MSWG ranked companies for the year 2007, 2008 and 2009. This study uses eight board profile characteristics, namely board age, board tenure, multiple directorship, education background, experience, financial expertise, ethnicity and gender diversity. By utilizing two different measures of earnings quality, this study finds that (i) financial expertise is positively related to earnings quality and (ii) multiple directorship and board tenure are negatively related to earnings quality. Overall, the result shows that firms with board of directors who possess certain criteria, namely financial expertise, number directorship and term of tenure would impact the quality of earnings.